2005
DOI: 10.1021/op049782x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control by Use of Near-IR for a Hydrogenation Process

Abstract: We applied process analytical technologies to solve the problem of selectivity in the hydrogenation of 3-(2-chloroethyl)-9-hydroxy-2-methyl-4H-pyrido[1,2-a]pyrimidin-4-one monohydrochloride (1) to (±)3-(2-chloroethyl)-6,7,8,9-tetrahydro-9-hydroxy-2-methyl-4H-pyrido[1,2-a]pyrimidin-4-one monohydrochloride (2). We showed that both mid-IR and near-IR (NIR) were suitable for in-line analysis of the hydrogenation. We chose to use NIR in the production environment due to easier implementation. We developed a NIR mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In recent years, some particle analysis techniques (PATs) have been widely used to monitor and control the transformation process during crystallization, especially in pharmaceutical, fine chemical, and food industries. , Off-line techniques such as powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermo gravimetric analysis (TGA), and scanning electron microscopy (SEM) are often used to identify the polymorphs to qualitatively analyze this process. , In situ techniques including focused beam reflectance measurement (FBRM), Raman spectroscopy, , attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR), and near-infrared (NIR) spectroscopy can be applied to analyze the transformation kinetics quantitatively. Particle vision measurement (PVM) can be used to follow the evolution of crystal morphology during the process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some particle analysis techniques (PATs) have been widely used to monitor and control the transformation process during crystallization, especially in pharmaceutical, fine chemical, and food industries. , Off-line techniques such as powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermo gravimetric analysis (TGA), and scanning electron microscopy (SEM) are often used to identify the polymorphs to qualitatively analyze this process. , In situ techniques including focused beam reflectance measurement (FBRM), Raman spectroscopy, , attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR), and near-infrared (NIR) spectroscopy can be applied to analyze the transformation kinetics quantitatively. Particle vision measurement (PVM) can be used to follow the evolution of crystal morphology during the process.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, a series of articles in a special section of the journal Organic Process Research & Development (OPR&D) demonstrated the potential of PAT framework in various operations within pharmaceutical process development and manufacturing. These articles cover reaction monitoring [161][162][163][164] crystallization, 161,165 granulation, 161 calorimetry and safety studies, 163 and in situ cleaning validation. 166 Since then, OPR&D had served as a regular platform for reporting new PAT technologies and applications.…”
Section: Publications Conferences and Internetmentioning
confidence: 99%
“…They also provide continuous real-time monitoring and are much more amenable to use in large scale manufacturing. 5,6 Whatever measurement system is used, the aim is clear, to gain process understanding and develop robust processes such that in-process measurements are only required where benefits can be realised, such as controlling critical process parameters and potentially reduce end product testing. Therefore, many of the measurement systems used in process development can often become embedded in the control strategy for a manufacturing process, so it is important that the measurement system itself is reliable and robust.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as MS, NMR and HPLC can provide detailed process understanding in early stages of development and are widely used, mostly off-line but increasingly using more at-line and on-line modes. Optical spectroscopic techniques can also be used as in-line measurement systems and offer some advantages over traditional off-line techniques for processes that are difficult to sample (heterogeneous, low temperature, unstable intermediates). They also provide continuous real-time monitoring and are much more amenable to use in large scale manufacturing. , Whatever measurement system is used, the aim is clear, to gain process understanding and develop robust processes such that in-process measurements are only required where benefits can be realised, such as controlling critical process parameters and potentially reduce end product testing. Therefore, many of the measurement systems used in process development can often become embedded in the control strategy for a manufacturing process, so it is important that the measurement system itself is reliable and robust.…”
Section: Introductionmentioning
confidence: 99%